Evolution of Liver Resection for Hepatocellular Carcinoma: Change Point Analysis of Textbook Outcome over Twenty Years - Yeshong Park; Ho-Seong Han; Seung Yeon Lim; Hyelim Joo; Jinju Kim; MeeYoung Kang; Boram Lee; Hae Won Lee; Yoo-Seok Yoon; Jai Young Cho (Medicina)
Background and Objectives: The aim of this study was to comprehensively analyze the evolution in textbook outcome (TO) achievement after liver resection for hepatocellular carcinoma (HCC) over two decades at a single tertiary referral center. Materials and Methods: All consecutive liver resections for HCC at Seoul National University Bundang Hospital from 2003 to 2022 were analyzed. The included 1334 patients were divided into four groups by time intervals identified through change point analysis. TO was defined as no intraoperative transfusions, positive margins, major complications, 30-day readmission or mortality, and prolonged length of hospital stay (LOS). Results: Multiple change point analysis identified three change points (2006, 2012, 2017), and patients were divided into four groups. More recent time interval groups were associated with older age (59 vs. 59 vs. 61 vs. 63 years, p < 0.0001) and more comorbidities. Minimally invasive procedures were increasingly performed (open/laparoscopic/robotic 37.0%/63.0%/0%) vs. 43.8%/56.2%/0% vs. 17.1%/82.4%/0.5% vs. 22.9%/75.9%/1.2%, p < 0.0001). TO achievement improved over time (1.9% vs. 18.5% vs. 47.7% vs. 62.5%, p < 0.0001), and LOS was the greatest limiting factor. Conclusions: TO after liver resection improved with advances in minimally invasive techniques and parenchymal sparing procedures, even in older patients with more comorbidities and advanced tumors.